The Reading Frequency and Literal Comprehension: A Study of Eighth Grade Students in Palu - Nila Utari Setiani; Abd. Kamaruddin; Hastini Hastini; Mochtar Marhum (MASI Mandiri Edukasi, 2025)
This study examined the correlation between reading frequency and reading comprehension, particularly at the literal level, among eighth-grade students at SMP Labschool UNTAD Palu, as regular reading practice can strengthen word recognition, vocabulary, and the ability to grasp explicit information in texts. This study was conducted in the even semester of the 2024/2025 academic year using a Pearson Product-Moment correlation design. A total of 36 students were selected through stratified random sampling. Data were collected using a reading frequency questionnaire and a reading comprehension test of 15 multiple-choice items based on descriptive texts from the Eighth-Grade syllabus. Instrument validity was tested using Pearson’s r, and reliability was analysed using Cronbach’s Alpha. All questionnaire items were declared valid, and the reliability analysis produced a Cronbach’s Alpha value of 0.743, indicating high internal consistency. There was a significant, moderate positive correlation between reading frequency and literal reading comprehension (r = 0.427; p = 0.009 (p < 0.05), indicating that increased reading frequency is associated with increased literal comprehension. The results of this study indicate that high reading frequency positively contributes to students' ability to identify explicit information in reading texts. This research strengthens the literature on basic literacy and can be a reference in developing a literacy-based curriculum at the junior high school level.